Piezoelectric hydrogel microneedle for promoting bone regeneration and preparation method thereof
Patent Information
- Application Number
- CN202610986748.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]因此,本领域亟需研发一款适配牙周治疗场景、可精准响应牙周修复微环境,兼具压电响应与多重修复功能的新型智能微针,实现对牙周炎症与骨缺损的协同治疗,解决现有产品功能单一、力学性能偏弱、药物释放不可控、骨修复效率低等问题
[0020](1)压电响应与超声增强:可响应口腔内源性力学信号产生电信号,配合外部超声能够进一步提升电信号强度与作用深度,有效调控牙周成骨进程、缓解局部炎症;
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical materials and technology, specifically relating to a method for preparing lipoic acid-sulfurized chitosan piezoelectric gel microneedles for periodontal bone defect repair. Background Technology
[0002] Periodontal disease is the leading cause of tooth loss in adults. It is characterized by chronic inflammation of the periodontal tissues, which gradually leads to periodontal bone destruction and bone resorption, severely impairing oral mastication function and oral health. Currently, non-surgical methods such as mechanical cleaning and local and systemic drug administration are commonly used to treat periodontal disease. However, these methods can only suppress the development of inflammation and are difficult to effectively repair existing periodontal bone defects and promote bone regeneration. Periodontal bone damage repair remains a major challenge in the treatment of periodontal disease.
[0003] Piezoelectric materials can generate electrical signals through mechanical stimulation, mimicking the natural electrophysiological microenvironment of bone in vivo. This effectively promotes osteoblast proliferation, differentiation, and bone matrix mineralization, and regulates local inflammatory responses. Although existing piezoelectric bone repair materials can enhance the output of electrical signals with the help of external ultrasound, the ultrasound stimulation mode is singular and cannot fully utilize the endogenous mechanical changes generated by the body's own activities. The targeting and duration of action are still insufficient.
[0004] Gel microneedles, with their large specific surface area, gentle insertion, precise drug delivery, and excellent biocompatibility, are ideal carriers for minimally invasive drug delivery to the oral mucosa. Combining the piezoelectric effect with multifunctional microneedles to create integrated microneedles that respond to endogenous mechanical signals and simultaneously achieve anti-inflammatory and antioxidant effects, piezoelectric bone promotion, and controlled drug release is of great significance for improving the repair of periodontal bone defects and optimizing the local microenvironment. However, currently, there are no dedicated intelligent microneedle products on the market that simultaneously possess piezoelectric response, controlled drug release, high mechanical strength, and excellent biocompatibility.
[0005] Therefore, there is an urgent need in this field to develop a new type of intelligent microneedle that is suitable for periodontal treatment scenarios, can accurately respond to the periodontal repair microenvironment, and has both piezoelectric response and multiple repair functions, so as to achieve synergistic treatment of periodontal inflammation and bone defects and solve the problems of existing products such as single function, weak mechanical properties, uncontrollable drug release, and low bone repair efficiency. Summary of the Invention
[0006] This invention aims to overcome the shortcomings of existing technologies and develop a thioctic acid-sulfurized chitosan piezoelectric gel microneedle. This product has a simple preparation process, controllable cost, and stable performance. It can effectively improve the repair effect of periodontal bone defects, reduce patient suffering and medical costs, and has significant clinical significance and broad market prospects for promoting the technological upgrading and clinical application of periodontal restorative microneedle products.
[0007] To achieve the above objectives, the present invention provides a piezoelectric gel microneedle for promoting bone regeneration and a method for preparing the same, comprising the following steps:
[0008] Step S1: Mix a certain mass ratio of sulfurized chitosan aqueous solution with a dimethyl sulfoxide solution of lipoic acid, add a certain amount of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride / N-hydroxysuccinimide (EDC / NHS) crosslinking agent, react for a certain time, and obtain lipoic acid-sulfurized chitosan by dialysis and freeze drying.
[0009] Step S2: Mix a certain volume ratio of polyvinyl alcohol aqueous solution with thioctic acid-sulfurized chitosan aqueous solution, add a thermal crosslinking agent for thermal crosslinking, and obtain a polyvinyl alcohol crosslinked thioctic acid-sulfurized chitosan solution at a certain temperature and time; then, add plant-derived anti-inflammatory active extract and piezoelectric nanoparticles to the solution, and ultrasonically disperse them evenly to obtain a mixed solution.
[0010] Step S3: Inject the above mixed solution into a microneedle polydimethylsiloxane (PDMS) mold, and after centrifugation, ultraviolet cross-linking, drying, and aseptic demolding, obtain piezoelectric gel microneedles with piezoelectric response, controllable drug release, high mechanical strength, and good biocompatibility.
[0011] Preferably, the concentration of the sulfurized chitosan is 1wt%~5wt%; the concentration of lipoic acid is 1wt%~10wt%; and the mass ratio of sulfurized chitosan to lipoic acid is 20:1~1:1.
[0012] Preferably, the crosslinking agent is EDC to NHS in a molar ratio of 1:1 to 10:1, and its addition amount is 20wt% to 50wt% of the mass of sulfurized chitosan, with a reaction time of 1 to 5 hours.
[0013] Preferably, the concentration of the thioctic acid-sulfurized chitosan aqueous solution is 0.5wt%~10wt%, the concentration of the polyvinyl alcohol aqueous solution is 1wt%~20wt%, and the volume ratio of the two is 1:5~3:1.
[0014] Preferably, the thermal crosslinking agent is one or more of glutaraldehyde, boric acid and trimethyl orthoformate, and the amount added is 0.5wt% to 5wt% of the total mass of the two, the crosslinking temperature is 40℃ to 90℃, and the crosslinking time is 10min to 60min.
[0015] Preferably, the plant-derived anti-inflammatory active extract contains one or more of rhein, aloe-emodin, quercetin, and curcumin, with a concentration of 0.3wt% to 1.5wt%; the piezoelectric nanoparticles are selected from one or more of barium titanate, zinc oxide, barium strontium titanate, and sodium potassium niobate, with a concentration of 0.1wt% to 2.0wt%.
[0016] Preferably, in the mixed solution PDMS microneedle mold, the tip shape of the microneedle mold is a cone, a triangular pyramid or a regular square pyramid, and its rotation speed is 3000rpm~7000rpm, centrifuged for 1min~10min, then the air bubbles and excess gel mother liquor are removed, dried and solidified, and then demolded.
[0017] Preferably, the ultraviolet lamp irradiation lasts for 1 to 8 minutes, and the drying temperature is 20-60℃ for drying and shaping.
[0018] The present invention also provides a lipoic acid-sulfurized chitosan piezoelectric gel microneedle and its application in the treatment of periodontal bone defects.
[0019] The lipoic acid-sulfurized chitosan piezoelectric gel microneedles prepared in this invention have the following beneficial effects:
[0020] (1) Piezoelectric response and ultrasound enhancement: It can generate electrical signals in response to the intrinsic mechanical signals in the oral cavity. Combined with external ultrasound, it can further enhance the intensity and depth of the electrical signal, effectively regulate the periodontal bone formation process and relieve local inflammation;
[0021] (2) Controllable structure and performance: The mechanical strength and molding effect of microneedles are improved by using polyvinyl alcohol crosslinking system. The sulfurized chitosan grafted with thioctic acid can optimize the hydrophilicity, biocompatibility and antibacterial properties of the material, while achieving stable drug release.
[0022] (3) Simple preparation and scalable: The process of solution blending, cross-linking and centrifugal molding is adopted. The reaction conditions are mild and the production process is simple, which facilitates mass production and clinical application.
[0023] (4) Synergistic repair through multiple mechanisms: relying on the antioxidant properties of lipoic acid-sulfurized chitosan, the anti-inflammatory effects of plant extracts, and the osteogenic effect of piezoelectric materials, multiple mechanisms work together to promote cell migration and osteogenic differentiation, and help periodontal tissue repair and regeneration.
[0024] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0025] Figure 1 This is a microscopic morphology diagram of the piezoelectric gel microneedles prepared in Example 2 of the present invention.
[0026] Figure 2 This is a microscopic morphology diagram of the piezoelectric gel microneedles prepared in Example 3 of the present invention. Detailed Implementation
[0027] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.
[0028] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.
[0029] Example 1
[0030] A method for preparing lipoic acid-sulfurized chitosan piezoelectric gel microneedles specifically includes the following steps:
[0031] Prepare a 1wt% sulfurized chitosan aqueous solution and a 1wt% thioctic acid dimethyl sulfoxide solution, and mix them evenly at a volume ratio of 20:1; add EDC / NHS (molar ratio 4:1), the amount of which is 40% of the mass of sulfurized chitosan, react at room temperature for 3 hours, dialysis purification, and freeze drying to obtain sulfurized chitosan grafted with thioctic acid.
[0032] Prepare a 20wt% polyvinyl alcohol aqueous solution and mix it with a 6wt% graft product aqueous solution at a volume ratio of 1:1. Let it stand to remove bubbles. Inject it into a regular square pyramidal PDMS microneedle mold, centrifuge at 3000rpm for 1min to remove bubbles and excess mother liquor. Crosslink it with 365nm ultraviolet light for 3min, dry it at 40℃ for 24h, and demold it aseptically.
[0033] The mechanical properties of the hydrogel microneedle patch prepared in this embodiment were verified using a universal mechanical testing machine; the puncture performance was verified using 3% agarose gel to simulate skin. The results showed that the obtained microneedle tips had poor formability and many breaks, with an average tip strength of about 0.03 N, which is lower than the strength required for skin puncture (0.07 N), directly causing the hydrogel microneedle patch to fail to penetrate the simulated skin.
[0034] Example 2
[0035] A method for preparing lipoic acid-sulfurized chitosan piezoelectric gel microneedles specifically includes the following steps:
[0036] Prepare a 1wt% sulfurized chitosan aqueous solution and a 1wt% thioctic acid dimethyl sulfoxide solution, and mix them evenly at a volume ratio of 20:1; add EDC / NHS (molar ratio 4:1), the amount of which is 40% of the mass of sulfurized chitosan, react at room temperature for 3 hours, dialysis purification, and freeze drying to obtain sulfurized chitosan grafted with thioctic acid.
[0037] Prepare a 20wt% polyvinyl alcohol aqueous solution and mix it with a 6wt% graft product aqueous solution at a volume ratio of 1:1. Add 3wt% trimethyl orthoformate, perform thermal crosslinking at 60℃ for 30 min, and allow to stand to remove bubbles. Inject the mixture into a regular square pyramidal PDMS microneedle mold, centrifuge at 3000 rpm for 1 min to remove bubbles and excess mother liquor. Perform ultraviolet crosslinking at 365 nm for 3 min, dry at 40℃ for 24 h, and aseptically demold.
[0038] The mechanical properties of the hydrogel microneedle patch prepared in this embodiment were verified using a multi-stage mechanical testing machine; the puncture performance was verified using 3% agarose gel to simulate skin. The results showed that the obtained microneedles... Figure 1 As shown, the needle tips are evenly distributed and uniform in size, with an average tip strength of approximately 8N, far exceeding the strength required for skin puncture (0.07N). This allows the needles to penetrate simulated skin smoothly while maintaining structural integrity, demonstrating excellent mechanical properties and clinical application potential.
[0039] Example 3
[0040] A method for preparing lipoic acid-sulfurized chitosan piezoelectric gel microneedles specifically includes the following steps:
[0041] Prepare a 1wt% sulfurized chitosan aqueous solution and a 1wt% thioctic acid dimethyl sulfoxide solution, and mix them evenly at a volume ratio of 20:1; add EDC / NHS (molar ratio 4:1), the amount of which is 40% of the mass of sulfurized chitosan, react at room temperature for 3 hours, dialysis purification, and freeze drying to obtain sulfurized chitosan grafted with thioctic acid.
[0042] Prepare a 20wt% polyvinyl alcohol aqueous solution and mix it with a 6wt% graft product aqueous solution at a volume ratio of 1:1. Add 3wt% trimethyl orthoformate, perform thermal crosslinking at 60℃ for 30 min, and allow to stand to remove bubbles. Add 1wt% barium titanate piezoelectric nanoparticles and ultrasonically disperse until uniform and stable. Inject into a square pyramidal PDMS microneedle mold, centrifuge at 3000rpm for 1 min to remove bubbles and excess mother liquor. Perform ultraviolet crosslinking at 365nm for 3 min, dry at 40℃ for 24 h, and aseptically demold.
[0043] The hydrogel microneedle patch containing nanoparticles but without drugs was named BP. The mechanical properties of the hydrogel microneedle patch prepared in this example were verified using a multi-stage mechanical testing machine. The results showed that the obtained BP microneedles... Figure 2 As shown, the addition of piezoelectric particles resulted in good moldability and increased mechanical strength of the microneedle patch, with an average tip strength of approximately 18 N. An electrochemical workstation and a standard three-electrode system were used to test the open-circuit current response of the microneedles under different ultrasonic powers. Results showed that the output current of the microneedles gradually increased with increasing ultrasonic power. Under 0.3 W ultrasonic conditions, the current of a single microneedle could increase by 0.22 mA, continuously releasing electrical signals to promote periodontal bone regeneration and regulate inflammation. The product is convenient to use and has high patient compliance. The biocompatibility of the samples was also tested. Results showed that the BP cell survival rate on day three was 93%, all greater than 90%, indicating that BP has good biocompatibility.
[0044] Example 4
[0045] A method for preparing lipoic acid-sulfurized chitosan piezoelectric gel microneedles specifically includes the following steps:
[0046] Prepare a 1wt% sulfurized chitosan aqueous solution and a 1wt% thioctic acid dimethyl sulfoxide solution, and mix them evenly at a volume ratio of 20:1; add EDC / NHS (molar ratio 4:1), the amount of which is 40% of the mass of sulfurized chitosan, react at room temperature for 3 hours, dialysis purification, and freeze drying to obtain sulfurized chitosan grafted with thioctic acid.
[0047] Prepare a 20wt% polyvinyl alcohol aqueous solution and mix it with a 6wt% graft product aqueous solution at a volume ratio of 1:1. Add 3wt% trimethyl orthoformate, perform thermal crosslinking at 60℃ for 30 min, and allow to stand to remove bubbles. Add 1wt% barium titanate piezoelectric nanoparticles and 1wt% rhein plant-derived anti-inflammatory active extract, and ultrasonically disperse until uniform and stable. Inject into a square pyramidal PDMS microneedle mold, centrifuge at 3000rpm for 1 min to remove bubbles and excess mother liquor. Perform ultraviolet crosslinking at 365nm for 3 min, dry at 40℃ for 24 h, and aseptically demold.
[0048] The hydrogel microneedle patch with added nanoparticles and drugs was named RBP. The antibacterial properties of different samples were tested. Results showed that RBPP achieved a 100% bactericidal rate, demonstrating excellent antibacterial efficacy. The biocompatibility of the samples was tested. Results showed that on day 3, the cell survival rate of the RBP group reached 97%; the cell migration rate of the RBP group increased to 63%, indicating that the drug had no significant cytotoxicity and could promote cell migration. The staining of the samples during osteogenic induction was tested. Results showed that on day 7, the relative intensity of alkaline phosphatase staining in the RBP+US group was 2.3 times that of the control group; on day 28, the relative intensity of Alizarin Red staining in the RBP+US group was 1.5 times that of the control group, confirming that this microneedle can effectively promote periodontal osteogenic formation.
[0049] Example 5
[0050] A method for preparing lipoic acid-sulfurized chitosan piezoelectric gel microneedles specifically includes the following steps:
[0051] Prepare a 1 wt% sulfurized chitosan aqueous solution and a 1 wt% thioctic acid dimethyl sulfoxide solution, and mix them evenly at a volume ratio of 10:1; add EDC / NHS (molar ratio 4:1), the amount of which is 40% of the mass of sulfurized chitosan, react at room temperature for 3 h, dialysis purification, and freeze drying to obtain sulfurized chitosan grafted with thioctic acid.
[0052] Prepare a 20wt% polyvinyl alcohol aqueous solution and mix it with a 4wt% graft product aqueous solution at a volume ratio of 1:1. Add 2wt% trimethyl orthoformate, perform thermal crosslinking at 60℃ for 30 min, and allow to stand to remove bubbles. Add 1wt% barium titanate piezoelectric nanoparticles and 1wt% rhein plant-derived anti-inflammatory active extract, and ultrasonically disperse until uniform and stable. Inject into a square pyramidal PDMS microneedle mold, centrifuge at 3000rpm for 1 min to remove bubbles and excess mother liquor. Perform ultraviolet crosslinking at 365nm for 3 min, dry at 40℃ for 24 h, aseptically demold, and apply ultrasound during in vitro biocompatibility testing.
[0053] The cell group subjected to ultrasound via hydrogel microneedle patches was named RBP+US. The biocompatibility of the samples was tested. Results showed that on day 3, the cell viability of the RBP+US group reached 105%; the cell migration rate of the RBP+US group increased to 90%, indicating that the piezoelectric effect and drug synergy can significantly promote cell migration. The staining of the samples during osteogenic induction was also tested. Results showed that on day 7, the relative intensity of alkaline phosphatase staining in the RBP+US group was 3.2 times that of the control group; on day 28, the relative intensity of alizarin red staining in the RBP+US group was 2.9 times that of the control group, confirming that ultrasound-synergistic piezoelectric response can further enhance periodontal osteogenic induction.
[0054] Experimental Example 1
[0055] 1wt%, 2wt%, 3wt%, 4wt%, and 5wt% sulfurized chitosan aqueous solutions and 1wt%, 3wt%, 5wt%, 9wt%, and 9wt% thioctic acid dimethyl sulfoxide solutions were prepared and mixed evenly at volume ratios of 20:1, 15:1, 10:1, 5:1, and 1:1, respectively. EDC / NHS (molar ratios of 2:1, 4:1, 6:1, 8:1, and 10:1) were added at amounts of 20%, 25%, 30%, 40%, and 50% of the mass of sulfurized chitosan, respectively. The mixtures were reacted at room temperature for 1h, 2h, 3h, 4h, and 5h, respectively. After dialysis purification and freeze-drying, thioctic acid-grafted sulfurized chitosan was obtained.
[0056] 1%, 5wt%, 10wt%, 15wt%, and 20wt% polyvinyl alcohol aqueous solutions were prepared, and mixed with 0.5wt%, 10wt%, 2wt%, 4wt%, 8wt%, and 10wt% graft product aqueous solutions at volume ratios of 3:1, 2:1, 1:1, 1:2, and 1:3, respectively. Trimethyl orthoformate was added at total mass of 1wt%, 2wt%, 3wt%, 4wt%, and 5wt%, respectively, and the mixtures were thermally crosslinked at 40℃, 50℃, 60℃, 70℃, and 90℃ for 10 min, 20 min, 30 min, 40 min, and 50 min, respectively. In the solution, allow to stand to remove bubbles; add 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, and 2wt% barium titanate piezoelectric nanoparticles and 0.3wt%, 0.5wt%, 0.7wt%, 1wt%, and 1.5wt% rhein plant-derived anti-inflammatory active extracts, respectively, and ultrasonically disperse until uniform and stable; inject into a regular square pyramidal PDMS microneedle mold, centrifuge at 3000rpm~7000rpm for 1min~10min to remove bubbles and excess mother liquor; crosslink with 365nm ultraviolet light for 0.5~8min, dry at 20℃~60℃ for 24h, and aseptically demold.
[0057] The compressive properties of the prepared hydrogel microneedle patches were tested using a universal testing machine. The results showed that the single-needle strengths of the patches with 1wt%, 2wt%, 3wt%, 4wt%, and 5wt% trimethyl orthoformate were 3.22N, 12.52N, 10.00N, 9.48N, and 4.52N, respectively; while the single-needle strengths of the patches with 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, and 2wt% barium titanate piezoelectric nanoparticles were 14.90N, 15.70N, 22.72N, 19.61N, and 18.58N, respectively. Therefore, the microneedle patch prepared with 2wt% trimethyl orthoformate and 1wt% barium titanate piezoelectric nanoparticles was the optimal ratio, with a single-needle compressive strength of 22.72N.
[0058] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A piezoelectric gel microneedle for promoting bone regeneration and its preparation method, characterized in that, Includes the following steps: Step S1: Mix a certain mass ratio of sulfurized chitosan aqueous solution with a dimethyl sulfoxide solution of thioctic acid, add a certain amount of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride / N-hydroxysuccinimide (EDC / NHS) crosslinking agent, react for a certain time, and obtain thioctic acid sulfurized chitosan by dialysis and freeze drying. Step S2: Mix a certain volume ratio of polyvinyl alcohol aqueous solution with thioctic acid-modified chitosan aqueous solution, add a thermal crosslinking agent for thermal crosslinking, and obtain a polyvinyl alcohol-crosslinked thioctic acid-modified chitosan solution at a certain temperature and time; then, add plant-derived anti-inflammatory active extract and piezoelectric nanoparticles to the solution, and ultrasonically disperse them evenly to obtain a mixed solution. Step S3: Inject the above mixed solution into a microneedle polydimethylsiloxane (PDMS) mold, and after centrifugation, ultraviolet cross-linking, drying, and aseptic demolding, obtain piezoelectric gel microneedles with piezoelectric response, controllable drug release, high mechanical strength, and good biocompatibility.
2. The preparation method according to claim 1, characterized in that... In step S1, the concentration of sulfurized chitosan is 1wt%~5wt%; the concentration of lipoic acid is 1wt%~10wt%; and the mass ratio of sulfurized chitosan to lipoic acid is 10:1~1:
1.
3. The preparation method according to claim 1, characterized in that... The crosslinking agent mentioned in step S1 is EDC to NHS in a molar ratio of 1:1 to 10:1, and its addition amount is 20wt% to 50wt% of the mass of sulfurized chitosan, with a reaction time of 1 to 5 hours.
4. The preparation method according to claim 1, characterized in that... In step S2, the concentration of the thioctic acid-sulfurized chitosan aqueous solution is 0.5wt%~10wt%, the concentration of the polyvinyl alcohol aqueous solution is 1wt%~20wt%, and the volume ratio of the two is 1:5~3:
1.
5. The preparation method according to claim 1, characterized in that... The thermal crosslinking agent mentioned in step S2 is one or more of glutaraldehyde, boric acid and trimethyl orthoformate, and the amount added is 0.5wt%~5wt% of the total mass of the two, the crosslinking temperature is 40℃~90℃, and the crosslinking time is 10min~60min.
6. The preparation method according to claim 1, characterized in that... In step S2, the plant-derived anti-inflammatory active extract contains one or more of the following: rhein, aloe-emodin, quercetin, and curcumin, with a concentration of 0.3wt% to 1.5wt%; the piezoelectric nanoparticles are selected from one or more of the following: barium titanate, zinc oxide, barium strontium titanate, and potassium sodium niobate, with a concentration of 0.1wt% to 2.0wt%.
7. The preparation method according to claim 1, characterized in that... In the mixed solution PDMS microneedle mold described in step S3, the tip shape of the microneedle mold is a cone, a triangular pyramid, or a regular square pyramid, and its rotation speed is 3000 rpm to 7000 rpm, centrifuged for 1 min to 10 min.
8. The preparation method according to claim 1, characterized in that... In step S3, the product is irradiated with ultraviolet light for 1 to 8 minutes and dried at a temperature of 20-60°C to form the product.
9. The lipoic acid-sulfurized chitosan piezoelectric gel microneedles are prepared by the preparation method according to any one of claims 1 to 8.